Performance of Dhaka Bank Limited in comparison with 2nd generation banks and BASEL-III Accord - Rahman, Md. Sayadur (Brac University, 2020)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2019.